2021
DOI: 10.2147/ijgm.s336823
|View full text |Cite
|
Sign up to set email alerts
|

Study of Clinical Predictive Value and Immune Characterization of SLFN11 in Clear Cell Renal Cell Carcinoma

Abstract: Background: SLFN11 has been found to regulate the development and progression of a variety of cancers and is associated with drug therapy, while its role in clear cell renal cell carcinoma (ccRCC) remains unclear; therefore, the aim of this study was to investigate SLFN11 expression in ccRCC patients and its correlations with clinicopathological and immunological features. Methods: Gene profiles of ccRCC and the clinicopathological information of patients were downloaded from the TCGA database. Microarrays fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Additionally, Liu et al correlated the increased expression of immune checkpoint genes CTLA4 and CD244 with SLFN11. These associations indicate immune regulatory roles for SLFN11 that may have clinical translational implications for cancers suffering from immunosuppressive microenvironment [44].…”
Section: Schlafens and Immune Cellsmentioning
confidence: 93%
See 1 more Smart Citation
“…Additionally, Liu et al correlated the increased expression of immune checkpoint genes CTLA4 and CD244 with SLFN11. These associations indicate immune regulatory roles for SLFN11 that may have clinical translational implications for cancers suffering from immunosuppressive microenvironment [44].…”
Section: Schlafens and Immune Cellsmentioning
confidence: 93%
“…Recently, SLFN11 has been linked to the malignant phenotype of clear cell renal cell carcinoma (ccRCC) promoting tumor growth, migration, and invasion [43]. SLFN11 is highly overexpressed in ccRCC where it is associated with poor overall survival [44]. Wang et al demonstrated that SLFN11 promotes the PI3K/AKT pathway supporting the increase of cellular proliferation, migration, and invasion as compared to ccRCC cells that lack SLFN11.…”
Section: Schlafen 11mentioning
confidence: 99%